2015
DOI: 10.1063/1.4936777
|View full text |Cite
|
Sign up to set email alerts
|

Fermi orbital self-interaction corrected electronic structure of molecules beyond local density approximation

Abstract: The correction of the self-interaction error (SIE) that is inherent to all standard density functional theory (DFT) calculations is an object of increasing interest. In this article we apply the very recently developed Fermi-orbital based approach for the self-interaction correction (FOSIC) [1,2] to a set of different molecular systems. Our study covers systems ranging from simple diatomic to large organic molecules. We focus our analysis on the direct estimation of the ionization potential from orbital eigenv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
3
33
1
Order By: Relevance
“…Prior application of the FLO‐SIC method to atoms and molecules showed that there are repeating structural motifs for the FODs describing orbitals for core and valence electrons. As discussed previously, in the case of valence electrons, these structural motifs carry bonding information and are transferable between similar chemical bonding situations.…”
Section: Fermi‐orbital Descriptor Generatorsmentioning
confidence: 99%
“…Prior application of the FLO‐SIC method to atoms and molecules showed that there are repeating structural motifs for the FODs describing orbitals for core and valence electrons. As discussed previously, in the case of valence electrons, these structural motifs carry bonding information and are transferable between similar chemical bonding situations.…”
Section: Fermi‐orbital Descriptor Generatorsmentioning
confidence: 99%
“…The initial FODs need to be guessed before the first SCF step. Since it is found that FODs often represent chemical bonds and lone pairs [15,25], making the initial guess is usually simple in first-and second-row elements. We calculate the forces on the FODs after the SCF loop for electronic structures as described in Ref.…”
Section: Algorithmmentioning
confidence: 99%
“…Generally speaking the best approach is to fully optimize a geometry but as discussed by Hahn et al, there may be cases where density-functional approximations yield a qualitatively incorrect geometry [32]. However, it is generally posited that the S = 2 geometry for the Fe(II)-porphyrin is bent rather than planar.…”
Section: Theoretical and Computational Detailsmentioning
confidence: 99%
“…The Löwdin symmetric reorthonormalization procedure guarantees that each localized orbital {φ iσ } is similar to its parent Fermi Orbital in a least-squares sense, but each localized orbital now depends parametrically on all the Fermi-orbital descriptors and on the spin-density matrix, or, equivalently, on the Kohn-Sham orbitals. Early indications [32,43,[47][48][49][52][53][54] are that the FLO-SIC improves orbital energies and atomization energies in a wide class of systems.…”
Section: Fermi-löwdin Orbitals For Unitarily Invariant Sicmentioning
confidence: 99%
See 1 more Smart Citation